How Will Higher Minimum Wages Affect Family Life and Children’s Well-Being? - Hill, Heather D. (Child Dev Perspect, 2017)
In recent years, new national and regional minimum wage laws have been passed in the United States and other countries. The laws assume that benefits flow not only to workers but also to their children. Adolescent workers will most likely be affected directly given their concentration in low-paying jobs, but younger children may be affected indirectly by changes in parents’ work conditions, family income, and the quality of nonparental child care. Research on minimum wages suggests modest and mixed economic effects: Decreases in employment can offset, partly or fully, wage increases, and modest reductions in poverty rates may fade over time. Few studies have examined the effects of minimum wage increases on the well-being of families, adults, and children. In this article, we use theoretical frameworks and empirical evidence concerning the effects on children of parental work and family income to suggest hypotheses about the effects of minimum wage increases on family life and children’s well-being.